Emotional Exhaustion and Its Relationship with Professional Performance Among Faculty Members of the College of Education at the University of Hail - Al-Shammari, Rehab Mujzi; Al-Mutawea, Malkah Murdi; Al-Shammari, Bashayr Nawaf (Journal of Educational and Psychological Sciences, 2025)
This study aimed to explore the nature of the relationship between emotional exhaustion and professional performance among faculty members at the College of Education, University of Hail, in light of the increasing psychological and professional pressures within academic environments. The study adopted a descriptive-analytical approach, which is most suitable for such research purposes. The sample consisted of 138 faculty members, selected using simple random sampling, representing 86.25% of the total population of 160 faculty members. The study utilized the Emotional Exhaustion Scale developed by Ibrahim (2025), along with the Professional Performance Scale developed by Eisaoui (2019). The findings revealed high levels of both emotional exhaustion and professional performance among the participants. Furthermore, a strong and statistically significant positive correlation was found between the two variables. Based on these results, the study recommends the development of psychological support programs, activation of career counseling services, fair distribution of academic and administrative workloads, organization of stress management workshops, promotion of extracurricular activities, and reinforcement of a culture of recognition and motivation within the academic environment.
Keywords: Emotional Exhaustion; Professional Performance; University of Hail